Penerapan teknologi dalam optimalisasi layanan perbankan - bilal, imam jagat (Maliki Interdisciplinary Journal, 2025)
Digital transformation has significantly changed the face of the banking industry, prompting financial institutions to adopt cutting-edge technologies to meet customers' growing needs for fast, easy and secure services. This article examines the application of technologies such as artificial intelligence (AI), blockchain, big data analytics, and cloud computing in optimizing banking services. Through the application of these technologies, banks around the world can increase operational efficiency, improve customer experience, and strengthen data security. However, the implementation of these technologies is also faced with challenges such as high investment costs, strict regulations, and the need for new skills for the workforce. Through analysis of case studies and empirical data, this article demonstrates the positive impact of technology implementation, including increased financial inclusion and reduced fraud risk. The article concludes with recommendations for banks to continue to innovate and adapt to technological developments to maintain competitiveness in the digital era.